Capitalism, Patriarchy, Slavery, and Racism in the Age of Digital Capitalism and Digital Labour. (July 2018) - Fuchs, Christian
This article asks: How can understanding the relationship of exploitation and oppression inform the study of digital labour and digital capitalism? It combines the analysis of capitalism, patriarchy, slavery, and racism in order to analyse digital labour. The approach taken also engages with a generalization of David Roediger's wages of whiteness approach, Marxist feminism, Angela Davis's Marxist black feminism, Rosa Luxemburg, Kylie Jarrett's concept of the digital housewife, Jack Qiu's notion of iSlavery, Eileen Meehan's concept of the gendered audience commodity, and Carter Wilson and Audrey Smedley's historical analyses of racism and class. The article presents a typology of differences and commonalities between wage-labour, slave-labour, reproductive labour, and Facebook labour. It shows that the digital data commodity is both gendered and racialized. It analyses how class, patriarchy, slavery, and racism overgrasp into each other in the realm of digital capitalism. It also introduces the notions of the organic composition of labour and the rate of reproductive labour and shows, based on example data, how to calculate these ratios that provide insights into the reality of unpaid labour in capitalism.